Beliefs of women with fibromialgia - Ana Cláudia de Souza Leite; Elys Oliveira Bezerra; Ana Clara Patriota Chaves; Fabiane da Silva Severino Lima (Rev Rene)
This research aimed at identifying beliefs that permeate the painful experience of women with fibromyalgia, according to the Rokeach’s theory. We interviewed 42 women attended in a Clinic of Orthopedics and Traumatology in the state of Ceara. We used a questionnaire that inquired about spiritual beliefs, coping with pain and personal values. The features which were identified were the following: central beliefs of unanimous consensus; Belief in God and seek of support in religion, zero consensus related to feelings of fear and belief that God helps ease the pain. As for the belief in authorities, which were also identified, God comes first and then the family. This classification allowed the visualization of beliefs that can be changed, encouraging the health professional to guide the participation of the family in the treatment of fibromyalgia. We can infer that spiritual beliefs can help in the confrontation of fibromyalgia and contribute to good mental health by being constantly strengthened by women.